Konsistensi dan Persistensi dalam Menyampaikan Suara Kenabian - Stephanus Hartoyo (Sekolah Tinggi Theologia Nazarene Indonesia, 2015)
The prophets, or in our days, we call them pastors, or preachers are in difficult situation. They have to make up their minds. Compromising with “sin” is regarded more promising, it means life, prosperity, and a future. Unlike the 400 Baal prophets, Micaiah has become a perfect example for us today. No matter what the consequences, even if it means death, he is persistent and consistent in preaching and prophesying the truth. Preachers should only speak God’s word–the truth, rather than their own ideas!